Optimum Board Size for Indonesian Public Companies - Komang Ayu Krisnadewi; Wayan Pradnyantha Wirasedana (Institute of Research and Community Outreach - Petra Christian University, 2019)
This research aims to investigate variables affecting board size in public companies listed on the Indonesian Stock Exchange (IDX) and optimum board size which maximizes firm’s value measured by Price to Earnings Ratio (PER), Price to Book Value (PBV), and Tobin’s Q. Using 4,379 observations from 2007 to 2015 of IDX data, this research finds that liquidity, solvability, activity, and profitability affect board size significantly in quadratic form. In addition, it is suggested that the optimum board size for small companies is four directors while the size for big companies is six to seven directors.